Kepentingan Kinerja dan Kesesuaian dari Harga Edible Flower PT XXX bagi Konsumen - Suminartika, Eti; Djuendah, Endah; Fillah, Viandy Al (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Edible flowers are flowers that can be consumed, used as garnishes in food dishes.  The edible flower global market is growing, but domestic production shows a slower increase compared to non-edible flowers. The supply and demand for edible flowers is related to its price.  The aim of this research is to analyze the importance, performance and suitability of edible flowers price for consumers.   The research design used is a quantitative design. This research method uses a survey method. The analysis used descriptive statistical analysis; the sample was taken randomly. The research was carried out at PT XXX. The research results show: PT XXX determines the price of edible flowers primarily based on quality considerations, then based on benefit considerations.  The consumer's interest in paying the purchase price is primarily based on quality, the next consideration is quantity. Consumer prefer to pay edible flower especially the benefits of edible flowers, then the quality of edible flowers. Consumer opinion: The price of edible flower from PT XXX is not much cheaper than from other sellers, the price of edible flower according to consumers is relatively expensive